Electrochemistry and electron paramagnetic resonance spectroscopy of cytochrome c and its heme-disrupted analogs - Novak, David; Mojovic, Milos; Pavicevic, Aleksandra; Zatloukalova, Martina; Hernychova, Lenka; Bartosik, Martin; Vacek, Jan (Bioelectrochemistry, 2018)
Cytochrome c (cyt c) is one of the most studied conjugated proteins due to its electron-transfer properties and ability to regulate the processes involved in homeostasis or apoptosis. Here we report an electrochemical strategy for investigating the electroactivity of cyt c and its analogs with a disrupted heme moiety, i.e. apocytochrome c (acyt c) and porphyrin cytochrome c (pcyt c). The electrochemical data are supplemented with low-temperature and spin-probe electron paramagnetic resonance (EPR) spectroscopy. The main contribution of this report is a complex evaluation of cyt c reduction and oxidation at the level of surface-localized amino acid residues and the heme moiety in a single electrochemical scan. The electrochemical pattern of cyt c is substantially different to both analogs acyt c and pcyt c, which could be applicable in further studies on the redox properties and structural stability of cytochromes and other hemeproteins.
Keywords: Models, Molecular; molekulární modely; Animals; Cytochromes c; Protein Conformation; Cattle; elektronová paramagnetická rezonance; hem; elektrochemie; koně; Electron Spin Resonance Spectroscopy; Electrochemistry; Heme; skot; cytochromy c; konformace proteinů; Horses; zvířata